Analysis of Malay language essay writing strategy: application of levine motor planning - Mat Zain, Fazilah; Othman, Shamsudin; Md. Sabil, Azhar; Said, Rozita @ Radhiah (Human Resource Management Academic Research Society, 2019)
Writing skills are considered the most difficult skill to teach and comprehend by students. This skill needs a student to think the idea, construct the idea and put the idea appropriately in the writing text. Poor mastery the writing skills may cause the students to think that writing activity is burdensome, therefore the result is gray. Most of the teachers argue that the main problem in writing an essay is the inability of the students to create an idea based on the topic given. Students need to know about the importance of using strategy in essay writing. This concept paper analyzing the essay writing strategy based on Levine Motor Planning. It also discussed the benefits of applying Levine Motor Planning in essay writing strategy. This theory has explained in depth about the brain process during writing. Thus, this paper could be used as a good platform to the teachers who love to explore cognitive writing skill to understand one’s mind while they are writing.